2016
DOI: 10.1002/2016wr019084
|View full text |Cite
|
Sign up to set email alerts
|

Framework for event‐based semidistributed modeling that unifies the SCS‐CN method, VIC, PDM, and TOPMODEL

Abstract: Hydrologists and engineers may choose from a range of semidistributed rainfall‐runoff models such as VIC, PDM, and TOPMODEL, all of which predict runoff from a distribution of watershed properties. However, these models are not easily compared to event‐based data and are missing ready‐to‐use analytical expressions that are analogous to the SCS‐CN method. The SCS‐CN method is an event‐based model that describes the runoff response with a rainfall‐runoff curve that is a function of the cumulative storm rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The Soil Conservation Service Curve Number (SCS-CN) method (Mockus, 1972) has been popularly used for direct runoff estimation in engineering communities. Even though the SCS-CN method was obtained empirically (Ponce, 1996;Beven, 2012), it is often interpreted as an infiltration excess runoff model (Bras, 1990;Mishra and Singh, 1999). Yu (1998) showed that partial area infiltration excess runoff generation on a statistical distribution of soil infiltration characteristics provided a similar runoff generation equation to the SCS-CN method.…”
Section: Introductionmentioning
confidence: 99%
“…The Soil Conservation Service Curve Number (SCS-CN) method (Mockus, 1972) has been popularly used for direct runoff estimation in engineering communities. Even though the SCS-CN method was obtained empirically (Ponce, 1996;Beven, 2012), it is often interpreted as an infiltration excess runoff model (Bras, 1990;Mishra and Singh, 1999). Yu (1998) showed that partial area infiltration excess runoff generation on a statistical distribution of soil infiltration characteristics provided a similar runoff generation equation to the SCS-CN method.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with data‐driven models, process‐driven hydrological models can better capture the physical processes in a catchment and are an important tool to estimate the elements of the water cycle (Bárdossy, ). In particular, on the daily scale, process‐driven hydrological models are usually superior to data‐driven ones (Bartlett et al, ; L. Wang et al, 2017). Therefore, this study applied data mining techniques to improving the performance of process‐driven hydrological models.…”
Section: Introductionmentioning
confidence: 99%
“…However, O&C do not recognize the compatibility of their call with our framework, which accommodates different runoff mechanisms (including threshold-type runoff resulting from different hydrologic connections to the stream [e.g., Hewlett and Hibbert, 1967;McDonnell, 2006a, 2006b;McGuire and McDonnell, 2010]) as well as different data-derived distributions for describing soil and rainfall variability. Indeed, we are intrigued by the fact that previous process-based rainfall-runoff research may be converging on the idea that all runoff processes are ''the same,'' i.e., all threshold like via filling, spilling, loss along the flow path and ultimately connectivity of saturated areas [McDonnell, 2013;Ameli et al, 2015;Bartlett et al, 2016b]. If true, this could lead to interesting developments for dynamic and multiscale models and new guidance for what data to collect in the field.…”
Section: Key Pointsmentioning
confidence: 99%
“…C1-C5 and C7: A specific response to these points is made difficult by the fact that they, when correct, apply generically to most spatially implicit rainfall-runoff models. We only note that (i) obtaining data for the parameter distributions of our model is no more difficult than gathering the data (e.g., soil hydraulics) desired by O&C in their call to action, (ii) including rainfall intensity is certainly possible (as also stated in Bartlett et al [2016a]) and work is in progress to implement the time compression approximation [e.g., Rigby and Porporato, 2006;Liu et al, 1998] in this framework, (iii) capturing discontinuity of the rainfall field and systematic spatial nonuniformities is possible through mixed distributions [e.g., Sivapalan et al, 1997], and (iv) accommodating (nonrandom) heterogeneity is feasible as demonstrated by the framework adaptation to TOPMODEL [Bartlett et al, 2016b]. Figure 1.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation